Gender and Educational Level: Analysis of Elementary School Teacher Numerical Skills - I Gede Suprawata; Putu Nanci Riastini (Universitas Pendidikan Ganesha, 2022)
Various professions demand numeracy skills of at least level 3, including the teaching profession, but teacher numeracy ability data is currently not available. Numeracy is the ability to apply mathematical concepts to make decisions. This research aims to assess the numeracy ability of elementary school teachers based on gender and teacher education level. The school can use data on teacher numeracy skills to evaluate the implementation of numeracy literacy programs in schools. In this study, use a descriptive approach. A total of 27 primary school teachers were the subject of the study. Data collection used general and advanced numeracy test instruments, with 10 questions divided into 3 general numeracy questions and 7 advanced numeracy questions. The collected data was analyzed using descriptive statistical techniques by calculating frequency, average, and data trends. The study results were then presented in the form of a histogram and narrated. The result of this study was the numeracy ability of elementary school teachers classified as moderate. Female teachers have better numeracy skills than men. Teachers with S2 education levels have better numeracy skills than those with S1 education levels. Teacher numeracy skills need to be improved, especially in male teachers who have lower than female teachers. Professional development of teachers in the field of teacher numeracy literacy needs to be improved, and the development of numeracy literacy tests was required in order to measure teacher numeracy skills.